Ceramics As Product Of Technology And Art: A Case Study Of Archaeological Remains At Yikpabongo - Asamoah-Mensah, H. (University of Ghana, 2013)
The focus of this archaeological research is in the area of ceramic technology and art. The aims of this study is to analyze the data on ceramic technology and art, establish ceramic typology base on technological and stylistic attributes and to determine the source of clay raw material of the excavated ceramics. To achieve these goals, the research approach adopted includes archaeological and chemical compositional analysis so as to provide answers to the unsolved concerns. The recovered materials from mound D included: human and animal remains, potsherds, stone objects, postholes, floor and a pot. The findings for this work indicated that mound D was a habitational/settlement mound. The radiocarbon date indicated that the excavated mound was between 5th and 7th centuries AD. The analysis of the potsherds revealed that large quantities of the potsherds were undecorated. The surface treatment techniques discovered were red-slipping, burnishing, dyeing and hand-smoothing of the vessels. Decorations on the potsherds consist of grooves, incisions, punctates, roulettes and channeling. Two types of vessel forms (jars/bowls) were discovered. X-ray fluorescence analysis was conducted on the excavated ceramics from Yikpabongo. These were compared to clay from Fumbisi. The result indicated that Fumbisi was the most likely source of the clay used to manufacture the excavated ceramics. The study indicated that ceramic technology and artistic decorations are the manifestation of the interaction or interrelation between societal goals, ideology and human capabilities on one hand and their environment on the other hand at every given time. This data adds to the existing body of knowledge about ceramics from Yikpabongo in the areas of technology of pottery production and decorative art.
Thesis (MA)- University of Ghana, 2013